CDK1 phosphorylates WRN at collapsed replication forks - Valentina Palermo (Nature Portfolio, 2016)
End-resection of double strand DNA breaks is essential for pathway choice between non-homologous end-joining and homologous recombination. Here the authors show that phosphorylation of WRN helicase by CDK1 is essential for resection at replication-related breaks.